SWADAYA MASYARAKAT DI DESA MENTAWAK BARU KECAMATAN AIR HITAM KABUPATEN SAROLANGUN PROVINSI JAMBI TAHUN 2014-2015 - Jeni Suprapti; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This Study entitled “Governmental In Development In New Mentawak Black Water District Sarolangun Jambi Province Years 2014-2015”. Govermental organizations in the form of mutual assistance society provide either labor or donations are very influential in the development process in the village of New Mentawak. However, the non-govermental level is only running in 2014, with a self-made one of the pillars of development in the New Mentawak Village. In 2015, the non-governmental level decreases, it is because after their village funds obtained by New Mentawak Village. Problems found in this study is a non-governmental tends to decrease, due to community empowerment by the village government is also not optimal. The method used in this study is a qualitative method that describes the data descriptively. Data collection techniques used were interviews and secondary data analysis. While the source of the data used are primary data obtained from the study site in the form of research informants and further supported by secondary data. Based on the results of research conducted there are some findings that the villagers of the New Mentawak the process of self-help to development in the village of New Mentawak in 2014. However, the self-help level declined in 2015 due to the reliance by the Village Fund granted by the central government. While the government has also made efforts to improve the development process in the country, but not so optimal.Keyword : Village, New Mentawak Village, Development Village, Non-Governmental